Keberanian ekstrim tokoh utama dalam film Kirikou et La Sorciere karya Michel Ocelot - Sulistiawan, Pragusti Listia Arrimara; Ismail, Subur; Dewi, Evi Rosyani (Franconesia, 2023)
This research aims to gain an understanding regarding the extreme courage of the main character, Kirikou, in the film Kirikou et La Sorciere by Michel Ocelot, utilizing three characteristics of the extreme courage as defined by Souchon, Gardette, and Woronoff (2000) and Franco & Zimbardo (2011): Extremism, Resilience, and Understanding of Actions. The research method is content analysis using a qualitative approach, followed by descriptive exposition. The initial phase of analysis from Mayring's (2021) approach, consists of: one (1) creating and formulating research questions, also known as problem statements, two (2) categorizing or separating each category from the analysis of messages, three (3) gathering data and placing it within previously established categories, then classifying it, four (4) revising categories while ensuring reliability or the validity of the formative aspect, checked within each category, five (5) summative checking across all categories and six (6) interpreting results or drawing conclusions from each category. The research findings indicate the presence of twenty (20) data representing characteristics of extreme courage. Specifically, out of these twenty (20) data, nine (9) exemplify the trait of Resilience, seven (7) exemplify Extremism, and four (4) exemplify Understanding of Actions.